1993
DOI: 10.1177/036354659302100210
|View full text |Cite
|
Sign up to set email alerts
|

"Bone bruises" on magnetic resonance imaging evaluation of anterior cruciate ligament injuries

Abstract: Magnetic resonance imaging of the knees of 98 consecutive patients with clinically diagnosed anterior cruciate ligament injuries revealed 47 patients (48%) with focal signal abnormalities consistent with the diagnosis of a "bone bruise." Seventy-one percent of the magnetic resonance images taken within 6 weeks of injury demonstrated a bone bruise, whereas no scans done longer than 6 weeks after injury showed a bruise (P < 0.0001). Also significant was the tendency for lesions to be located in the lateral compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
2
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(149 citation statements)
references
References 13 publications
2
142
2
3
Order By: Relevance
“…ACL tears are associated with at least one bone bruise in 71% of patients, and most commonly involve the midportion of the lateral femoral condyle near the terminal sulcus and the posterior lateral tibial plateau [5]. Our incidence of bone bruises was even higher (88.6%).…”
Section: Discussionmentioning
confidence: 73%
“…ACL tears are associated with at least one bone bruise in 71% of patients, and most commonly involve the midportion of the lateral femoral condyle near the terminal sulcus and the posterior lateral tibial plateau [5]. Our incidence of bone bruises was even higher (88.6%).…”
Section: Discussionmentioning
confidence: 73%
“…The presence of bone bruises was first described by Mink et al [175] after reviewing MRI of the knee associated with medial collateral ligament (MCL) injuries. Mink et al [176] later reported that bone bruises in the lateral femoral condyle and/or lateral tibial plateau were observed in 72% of ACL injured knees, and this finding has been confirmed by other researchers [177][178][179][180][181][182][183][184][185][186][187]. Histological changes in the articular cartilage overlying a geographic bone bruise demonstrated significant injury to the homeostasis of the articular cartilage over the bone [183].…”
Section: Mri Analysesmentioning
confidence: 68%
“…Bone 'bruises', sustained at the time of injury, may perhaps damage the subchondral bone (Graf et al 1993;Fowler 1994). Even the geometry of the femoral condyle has been evoked (Friden et al 1993).…”
Section: Discussionmentioning
confidence: 99%